Produção de alfafa e teor de boro e nitrogênio na planta e em solo submetido a níveis de boro - Borba, Tatiana Caldas (2012)
The aim of this study was to evaluate the effect of the rates of boron on dry matter production of Alfalfa plants and their roots, and boron and nitrogen concentration in plants in an Oxisol in Paraná, Brazil. The experiment was conducted at Agronomic Institute of Paraná (IAPAR) in Pato Branco town, Paraná, Brazil, in the 2011 agricultural year. The experimental design to the Alfalfa dry matter production was randomized blocks, in subdivided plots, with collection dates and boron doses. To the analysis of root dry matter (RDM) the design a randomized block design was used with four replicates, and treatments of five doses of boron. For the soil the design was randomized block with the sub-divided plots with four replications. In which the main plots consisted of collections, five doses of B (0, 0.5, 1, 2, 4 kg ha-1) in the subplots and in the sub-subplots at 0-5, 5-10 and 10-20 cm depths. The largest dry matter production evaluated by sampling occurred in October 2011, with a production of 3.676,6 kg ha-1 and 131,31 kg ha-1 day-1, for dry matter and accumulation rate, respectively. In relation to the nutrients concentration in plants the highest average was found in January, with 81,37 mg kg-1 of boron concentration, and 44,39 mg kg- 1 of nitrogen, in October. The dry matter production of roots was not affected by boron levels. The highest average boron concentration at the soil was 0,17 mg kg-1. The highest average ammonia levels was 51.13 mg kg-1 of NH4 at the soil in the third collect. The most efficient technique for the nitrate was a dose of 2,14 kg of B ha-1, reaching 52,33 mg kg-1. Besides, an interaction between date and depth was observed from 39 to 54 mg kg-1.